Verbal fluency in school-aged Spanish children: analysis of clustering and switching organizational strategies, employing different semantic categories and letters - Sánchez López, María del Pino; Román Lapuente, Francisco; García-Rubio, María J. (Anales de Psicología / Annals of Psychology, 2021)
The verbal ﬂuency (VF) task is a measure of cognitive ﬂexibility and search strategy within the lexicon and semantic topic. In this work the use of organizational strategies, i.e., clustering and switching in semantic and phonological ﬂuency was tested in healthy Spanish children divided in two groups: group 1 of younger children (age 8–9) and group 2 of older children (age 10–11) introducing different letters (F, A, S and P, M, R) and semantic categories (animals and meals or drinks). Semantic ﬂuency was greater than phonological ﬂuency in both age groups. In addition, older children showed better performance of both fluencies than younger children specifically for FAS letters group, M letter and all of semantic categories used. From the phonological analyses, younger children evoked more word with the PMR letter group than with the FAS one. Moreover, an improvement of semantic fluency associated with the animal’s category faced to meals and drink was observed only in the younger children group. In respect to organizational strategies, older children used more switches specifically in FAS group and more clusters for the meals or drinks category compared with the older children group. To finish, the relationships between the number of words evoked and the number of clusters and switches for both VF tasks were significant and positive. These data suggest that the type of letter and the semantic category employed in the VF evaluation modulate the verbal fluency performance in both groups of age